O ensino de conteúdos sobre o sistema solar com aporte na aprendizagem baseada em equipes e em jogos pedagógicos - Costa, Cristiane Machado da (2018)
This work deals with a research of the type pedagogical intervention, based on a didactic sequence that seeks to introduce pedagogical games as a tool to assist in the teaching-learning process of Astronomy, with emphasis on the Solar System, based on the active method Team-Based Learning. The pedagogical intervention was carried out in a Municipal School of Primary Education in the city of Bagé, Rio Grande do Sul, with sixth year students of elementary school, having as educational product a didactic sequence containing three pedagogical games. The first game consists of a board where students traverse a trail receiving information about the History of Astronomy, with the purpose of motivating learning and introducing the games as a pedagogical resource in the teaching-learning process. The second game is a question and answer, providing the experimentation of doing work in teams during the science classes, planned for the teaching of Astronomy, where they worked on basic concepts of Astronomy. The third consists of a board game, aiming to verify the knowledge acquired during the process of implementation of the didactic sequence, about the structure and characteristics of the Solar System. In order to verify the effectiveness of the proposal, the activities developed were analyzed qualitatively and quantitatively. The learning gain method was used for a quantitative analysis of the data. For this, pre and post-tests were used in relation to the content on the Solar System. As a result, we identified a learning gain of 76%. The educational production of this work is a support material, containing a series of lessons, practical and experimental activities, three pedagogical games that can be used as support for teachers of basic science to teach classes about the solar system.